Yao.jl: Extensible, Efficient Framework for Quantum Algorithm Design - Luo, Xiu-Zhe; Liu, Jin-Guo; Zhang, Pan; Wang, Lei (Quantum (Vienna, Austria), 2020)
We introduce Yao , an extensible, efficient open-source framework for quantum algorithm design. Yao features generic and differentiable programming of quantum circuits. It achieves state-of-the-art performance in simulating small to intermediate-sized quantum circuits that are relevant to near-term applications. We introduce the design principles and critical techniques behind Yao . These include the quantum block intermediate representation of quantum circuits, a builtin automatic differentiation engine optimized for reversible computing, and batched quantum registers with GPU acceleration. The extensibility and efficiency of Yao help boost innovation in quantum algorithm design.